Pengaruh Aspek Keuangan Internal Perusahaan Terhadap Likuiditas Perusahaan Subsektor Media Dan Entertainment Yang Terdaftar Di BEI Tahun 2021-2022 - Widi, Rica Oktarisa; Yusrialis, Yusrialis (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
This study aims to see or prove that internal financial aspects such as cash turnover, accounts receivable turnover, inventory turnover and working capital turnover affect company liquidity. The publication of the annual report of each issuer in the media and entertainment subsector listed on the IDX in 2021-2022 is the main benchmark for this research data, which is often known as secondary data. With a total population and sample of 14 companies. In the data analysis process using panel data regression and common effect models with the help of eviews software version 10. The results obtained partially cash turnover, accounts receivable turnover and inventory turnover affect the liquidity of the company. While working capital turnover has no effect on company liquidity. Based on the simultaneous test, cash turnover, accounts receivable turnover, inventory turnover and working capital turnover have a significant effect on the liquidity of media and entertainment companies listed on the IDX in 2021-2022. With the acquisition of adjusted R² worth 0.4349 or 43.49%, it means that the independent variables in this study affect the dependent variable. Conversely, 56.51% of the independent variables outside the study affect the liquidity variable.